AVALIAÇÃO DE PROPRIEDADES DE UNIÃO DE ADESIVOS UNIVERSAIS AO CANAL RADICULAR PREPARADO COM DIFERENTES INSTRUMENTOS ROTATÓRIOS - Bakaus, Thaís Emanuelle (2016)
The objective of this study was to evaluate the influence of a rotating device used to prepare the root canal in the adhesion of glass fiber posts and evaluate different bonding strategies using universal adhesive systems. One hundred human premolars were used, which had their crowns removed and their roots endodontically treated. Initially, the roots were divided into four groups, according to a combination of the factors: a rotating device used to prepare the root canal - carbide bur (CB) and diamond bur (DB) and cementation system (universal adhesive system associated with its respective resin cement - Single Bond Universal / RelyX ARC (SB) and Prime&Bond elect / Enforce (PB). They were then divided into subgroups according to the bonding strategy: Self-etch (SE) or Etch-and-rise (E&R). Eight teeth per group were evaluated in bond strength (BS) by the push-out test and 4 in nanoleakage teeth (NL) by scanning electron microscopy (SEM), and the roots for these tests were transversely sectioned in 6 slices. The data of BS and NI for each cementation system were subjected to 2-way ANOVA and Tukey (α = 0.05). For BS, only the major factors were significant (p <0.05), and for both cementation systems, the highest BS values were observed for the preparation with DB compared to the CB and SE adhesion strategy compared with E&R. Likewise, the interaction was not significant for NL (p> 0.05). For the cementation system PB, the lowest values were observed for groups using DB compared to the CB and SE adhesion strategy compared to E&R. For the SB cementation system, only the rotating device main factor was significant (p = 0.01), whereas the DB resulted in lower average nanoleakage compared to the CB. It can be concluded that to improve the adhesion of glass fiber posts to root canal, diamond bur should be used to prepare the root canal; and, in general, universal adhesive systems must be used in self-etch mode to obtain satisfactory results on intracanal adhesion.